Modeling factors affecting the susceptibility of construction workers to accidents using structural equation model - Yahya Safaei; Habibollah Dehghan; Samane Khorshidikia; Ehsanollah Habibi (International Journal of Environmental Health Engineering, 2023)
Aim: Identifying the factors affecting the susceptibility to accident aiming to reach a better understanding of this phenomenon and review preventive strategies is of the utmost consequence. The present study was carried out with the aim to model the factors affecting the susceptibility of construction workers to an accident using the structural equation model. Materials and Methods: This research was of cross-sectional type which was conducted on 200 people in one of the construction sectors in one of the oil refineries from 2020 to 2021. Participants were divided into accident and nonaccident groups. Data were collected using demographic questions contained in 11 questionnaires in three individual, organizational, and social areas. SPSS and PLS-SEM software were also used for statistical analysis and modeling. Results: There was a significant relationship between the two groups in the final score of accident susceptibility, individual personality in the field of openness, and safety culture in the field of work environment (P < 0.05). The findings showed that job stress has a direct relationship with accident proneness and individual factors and social factors have an inverse relationship with accident proneness. Conclusion: After juxtaposing the data, in addition to identifying people with higher accident susceptibility, it can be concluded that industry managers should take into account the background and influencing factors which affect this variable to lessen the accidents. The managers are also requested to improve working conditions, provide the workers with more training, and examine individual and social factors in addition to taking safety measures.